Preparation and characterization of a new coagulant based on the sago starch biopolymer and its application in water turbidity removal - Qudsieh, I. Y. M.; Fakhru'l, Razi A.; Kabbashi, N. A.; Mirghani, M. E. S.; Fandi, K. G.; Alam, M. Z; Muyibi, Suleyman Aremu; Nasef, Mohamed Mahmoud (Wiley InterScience, 2008)

(untitled)
A new organic coagulant, sago starch (SS)-graft-polyacrylamide (PAm), was prepared by the cericion-induced redox polymerization of acrylamide (Am) onto SS at room temperature. The effects of the variation of the concentration of Am and the initiator on the percentages of yield and total conversion were investigated. The chemical composition, viscosity, and side-chain-average molecular weight of the obtained graft copolymers were determined. The newly obtained coagulant was tested for the treatment of the turbidity of water. The SS-g-PAm coagulants were found to achieve water turbidity removal up to 96.6%. The results of this study suggest that SS-gPAm copolymer is a potential coagulant for reducing turbidity during water treatment.